Out of the shadow of famine: Evolving food markets and food policy in Bangladesh - Ahmed, Raisuddin; Haggblade, Steven; Chowdhury, Tawfiq-e-Elahi (International Food Policy Research Institute, 2000)
This book describes how Bangladesh transformed its food markets and food policies to free the country from the constant threat of famine. Since 1990, the Bangladeshi government has dismantled its food rationing system, privatized grain distribution, eased restrictions on international trade, and reduced its own presence in grain markets. The foundation for these developments was laid in the preceding decades. Improvements in agricultural science in the 1970s roughly doubled farm yields, while in the 1980s liberalization of irrigation restrictions, the lifting of import barriers to irrigation technology, and the privatization of fertilizer distribution rapidly increased rice cultivation. These increases in production, coupled with improvements in infrastructure and a more slowly growing and increasingly urban population, have substantially changed the structure of food grain markets, leading to increased marketing volumes, lower prices, and significantly larger private grain stocks. The book sets the Bangladeshi case in the larger context of the South Asian subcontinent and other developing countries in Asia. The authors examine the shifting structure of supply and demand in the grain markets, the history of government intervention in those markets, and the more recent changes that altered the arguments for such intervention and led to policy changes. The case of Bangladesh also has more general relevance as a study of the outcomes of a market-oriented reform program.